TAX CONTROL IN THE FUNCTION OF THE PROTECTION OF FISCAL INTERESTS OF THE REPUBLIC OF SERBIA - Kulić, Mirko (NBP. Nauka, bezbednosti, policija, 2019)
Abstract: The paper deals with measures of preventive, corrective and repressive character undetraken by tax authorities in order to protect the fiscal interests of the Republic of Serbia. The aim of the research is to show that the amount of collected public revenues to a considerable extent depends on the correctness and accuracy of the work of tax authorities in the procedures of tax control. The autor points to the tax control carried out by the Tax Administration and tax control carried out by the competent authorities of local self-government units. The legistrator’s efforts to maintain a balance between wide powers the authorities have and corresponding obligations of taxpayers and other controlled persons, are also being pointed out. Primarily, the accent is on the right and duty of the tax inspector to, when certain conditions are fulfilled, take away goods from taxpayers and other controlled persons or temporarily prohibits the performance of their activities, as well as the fund of rights available to them to protect own interests. Keywords: tax control, tax inspector, taxpayer, seizure of goods, temporary ban of performing activities.